PENGARUH TEKANAN ANGGARAN WAKTU, KOMPLEKSITAS TUGAS, PENGETAHUAN AUDITOR, DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT (Studi Kasus Pada KAP di Pekanbaru, Batam, dan Padang) - Andini Rahmatika Putri; Azwir Nasir; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to test the Influence of Time Budget Pressure, Task Complexity, Knowledge Auditor, and Audit Judgment Against Auditor Experience. In this studied, data collected by using questionnaires given to auditors who work in Public Accounting Firm in Pekanbaru, Batam, and Padang. The data used are primary data. Data were collected through questionnaires. Data were analyzed using data analysis techniques to assess the outer SmartPLS models: Convergent Validity, Composite Discriminant Validity and Reliability. From the questionnaires sent many as 100 questionnaires (74%) that can be completed and processed. Accuracy auditor to generate audit judgement influenced by time budget pressure, task complexity, knowledge, and experience. The study population was all auditor who worked on the firm in Pekanbaru, Batam, and Padang, and has worked at least 2 year experience. The result of this study showed that time budget pressure, task complexity, knowledge, and experience has a positive influence on audit judgment. Suggestion for futher research that could add situational factors such as organizational culture and and ethical values as well as more variable.Keywords: time budget pressure, task complexity, knowledge, experience, and audit judgment